Legislative Changes for Economic Development on Regional Basis, the Possibilities or Conditions for the Integration of the West Balkan Countries in the European Union – Kosovo Case - KRASNIQI, Armand (Journal of Advanced Research in Law and Economics; Vol 4 No 2 (2013): JARLE Volume IV Issue 2(8) Winter 2013, 2016)
The most of countries covered by the territory of Western Balkan on the Constitution basis over the territory and governmental policies have regulate and systemise this policies on local and central level. These public regulations, even in the political and governmental plan can be functional but this is not argued in the development plan of Kosovo. The economic indicators of these countries, especially in Kosovo as in long transition economical-social country, are not encouraging and continually are under the influence of global crisis effects. The improvement of this situation is not expected to be encouraging on the contrary the chances to deepen the crisis are real. Under the influence of these circumstances these countries must redesign their own strategic development plans. The country development must be realized based totally on integration policies of the European Union and by looking the possibilities for a real economic development in the region and all country. Naturally, all this must be based on available resources and by making their revalorization. There is no possibility to implement these policies and strategies if are not accompanied with the changes of legislative basis which will create to the local governments possibilities to construct institutions respectively agencies of this character. Above all the philosophy and practices of European Union on the development are based on regional economy development.
Keywords: region; legislation; integration; economic development; government